Increased Pharyngeal Reflux in Patients Treated for Laryngeal Cancer: A Pilot Study. (November 2015) - LeBlanc, Blake; Lewis, Ellen; Caldito, Gloria; Nathan, Cherie-Ann O.
Objective: Laryngopharyngeal reflux may cause significant morbidity in the head and neck cancer population. The goal was to determine if pharyngeal reflux is increased as a result of treatment for laryngeal cancer. Study Design: A prospective clinical trial. Setting: Tertiary care center. Subjects: Head and neck cancer patients treated at LSU Health–Shreveport with a plan for total laryngectomy. Methods: Pharyngeal pH probes with resultant reflux scores were utilized in patients with laryngeal/pharyngeal cancer with a plan for total laryngectomy. Results: Twenty-four patients were enrolled, of whom 10 underwent postlaryngectomy pH probe monitoring. The mean upright Ryan score for patients with prior radiotherapy was 238.4 (n = 8), compared with 22.0 (n = 16) in those without prior radiotherapy ( P = .02). The supine score was 12.7 in the radiotherapy group and 2.7 in those without radiotherapy ( P = .12). For those who completed the postlaryngectomy pH study (n = 10), the mean preoperative upright Ryan score was 106.32 ± 279.1 versus a postoperative score of 209.0 ± 352.6 ( P = .04). The mean supine preoperative Ryan score in this group was 3.9 ± 3.47, as opposed to 8.1 ± 9.6 postoperatively ( P = .13) Conclusions: This study suggests that treatment of laryngeal cancer may increase the incidence of pharyngeal reflux. Consider screening for reflux in patients previously treated for laryngeal cancer.